Emerging Demands of Nutraceuticals (Functional Foods) Among the Women During Pandemic: An Intensive Exploratory Study - Banerjee Bhattacharya Mayuri (International Journal of Coronaviruses, 2022)
Corona pandemic resulted in huge burden on health care service sectors. Although pharmaceutical is the one of the largest industry in the world and predominant in health care services yet sudden outbreak of disease has questioned our ability of fighting back. The people across the globe have become more aware regarding health and wellness, hence they looking for other natural, reliable, affordable and available options. The nutraceuticals or functional foods are expected to have various health benefits and people are looking for more advance nutraceuticals for better immunity. An intensive exploratory study was conducted in one of the most reputed Banerjee’s Clinic located at Khamtarai region, Raipur, Chhattisgarh where 237 female participated in the questionnaire survey. The study result revealed that majority of women (52%) age 34-41 years use neutraceuticals for better health and to boost their immunity. Furthermore, the females who are working both public and private sectors and are financially independent are aware of health benefits of nutraceuticals/functional foods and spend on nutraceuticals for overall wellness. Moreover, the women preferred tablets form of nutraceuticals rather than powder or liquid form as mode of consumption.The study further shows that women who are professionals prefer to take daily functional foods or nutraceuticals for good health, immunity and beauty.
Keywords: Nutraceuticals preferences